Pengaruh Green Product dan Green Advertising Terhadap Keputusan Pembelian Deterjen Merek Attack di Kota Banda Aceh - Supardi (SUMBER INFORMASI MANAJEMEN BISNIS DAN AKUNTANSI, 2024)
This study aims to determine the influence of green product and green advertising on purchasing decisions for Attack Brand Detergent in Banda Aceh City. The study population was all Attack Brand Detergent consumers in Banda Aceh City, and the sampling technique used the Rao Purba formula, resulting in 96 consumers. The analysis used in this study was multiple linear regression analysis. The results showed that green product and green advertising simultaneously and partially had a significant influence on purchasing decisions for Attack Brand Detergent in Banda Aceh City. Green product partially had a significant influence on purchasing decisions for Attack Brand Detergent in Banda Aceh City, while green advertising partially had a significant influence on purchasing decisions for Attack Brand Detergent in Banda Aceh City. The implications of this study indicate that green product and green advertising play a significant role in increasing purchasing decisions. Therefore, it can be recommended that the company continue to maintain and improve product quality and varied advertising to attract consumers to buy Attack detergent products, thereby creating a high level of purchasing decision among consumers.